Study on the safety evaluation of latent tuberculosis treatment in high‑risk groups for tuberculosis development: Study protocol for a multi‑center prospective observational cohort study in Korea (STEP-TB) - Yunkyeong Hwang; Yeonhee Park; Hyung Woo Kim; Seo Yun Jeong; Yoolwon Jeong; Helen R. Stagg; Ju Sang Kim; Jinsoo Min (PLoS ONE, 2026)
Background Tuberculosis preventive treatment (TPT) is essential for tuberculosis elimination; however, evidence on its safety and feasibility in medically complex, high-risk populations is limited. Concerns regarding adverse events frequently hinder treatment initiation and completion in routine clinical practice. Objectives The Safety of Preventive Treatment in People at Risk for Tuberculosis (STEP-TB) study aims to generate real-world evidence on the safety of TPT among individuals at high risk of developing active tuberculosis disease and to identify factors associated with adverse events, treatment initiation, adherence, and completion. Methods STEP-TB is a multicenter, prospective observational cohort study conducted at four university-affiliated hospitals in the Republic of Korea. Adults aged ≥19 years who are eligible for latent tuberculosis infection (LTBI) testing or TPT according to national guidelines will be enrolled, including individuals with chronic kidney disease, chronic lung disease, diabetes mellitus, immunosuppressive conditions, malignancy, or occupational risk. LTBI testing will be performed using interferon-gamma release assays, and TPT regimens will follow national guidelines. Participants initiating TPT will be followed for up to 12 months from treatment initiation. Those with negative LTBI results or without TPT will be also followed for up to 12 months. Adverse events, treatment adherence, and completion will be systematically assessed. Blood samples, including volumetric absorptive microsampling, will be collected in a subset of participants for pharmacokinetic and pharmacogenetic analyses. Outcomes The primary outcome is the occurrence of adverse events during TPT. Secondary outcomes include TPT completion rates, predictors of non-initiation and discontinuation, and progression to active TB. Conclusion STEP-TB will provide condition-specific, real-world evidence on TPT safety and implementation, informing clinical decision-making, patient-centered care, and national TB control policies to support the safe expansion of LTBI treatment strategies in Korea. CRIS Registration Number: KCT0011063